2022
DOI: 10.3390/agriculture12091351
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Treatment Promoted Callus Formation on Postharvest Sweet Potato by Adjusting Active Oxygen and Phenylpropanoid Metabolism

Abstract: This study aimed to investigate that rapid high-temperature treatment (RHT) at an appropriate temperature could accelerate callus formation by effectively promoting the necessary metabolic pathways in sweet potato callus. In this study, the callus of sweet potato was treated with heat shock at 50, 65, and 80 °C for 15 min. The callus formation was observed within 1, 3, and 5 days, and the accumulation of intermediates in the metabolism of phenylpropane and reactive oxygen species and changes in enzyme activiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…Hydrogen peroxide (H 2 O 2 ) content was tested according to [ 24 , 25 ] with some modifications. Apricot flesh tissue (10 g) was homogenized in 5 mL of cold acetone and centrifuged at 10,000× g and 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogen peroxide (H 2 O 2 ) content was tested according to [ 24 , 25 ] with some modifications. Apricot flesh tissue (10 g) was homogenized in 5 mL of cold acetone and centrifuged at 10,000× g and 4 °C for 30 min.…”
Section: Methodsmentioning
confidence: 99%
“…The determination of 1,1-dipheny1-2-Picryl-Hydrazyl (DPPH) clearance capacity referred to Xin et al [ 25 ] and was modified; 5 g of frozen callus were taken and placed in a centrifuge tube (50 mL). The 20 mL ethanol (70%) solution was added, mixed, and ultrasonically treated for 1 h, centrifuged (4 °C 10,000× g 20 min), and the supernatant was taken as the extract.…”
Section: Methodsmentioning
confidence: 99%
“…Since heat stress can influence the metabolic processes that enable callus formation, a study investigated the effect of rapid high-temperature (RHT) treatment at 50, 65, and 80 • C on sweet potato tubers [6]. The results showed that appropriate RHT treatment at 65 • C can stimulate the metabolism of reactive oxygen species (ROS) at the injury site of sweet potato on the first day.…”
Section: Special Issue Overviewmentioning
confidence: 99%
“…Chlorogenic acid (CGA) has been identified as a critical factor in combating oxidative stress in plants. In the autumn, plants experience various stressors such as lower temperatures, a reduced light intensity, and altered photoperiods, all of which can lead to the production of reactive oxygen species (ROS) [54,55]. Higher levels of chlorogenic acid help mitigate the damaging effects of these reactive molecules.…”
Section: Changes In the Chemical Constituents In The Leaves Of A Elat...mentioning
confidence: 99%